An Unilateral Rectus Sternalis Muscle: It`s Clinical Significance. - Raju S,; Raghu J,; Sreenivasulu Reddy M,; Sirisha B,; Indira B,; Sujata M, (Department of Surgery, UKM Medical Centre, 2012)
Knowledge concerning the variations of chest wall musculature is imperative for Surgeons, Radiologists and Anatomists. Rectus sternalis is a variant chest wall muscle found in the anterior thoracic wall along the side of sternum. The presence of this muscle may be mistaken for tumor on mammogram, and causes implications during mastectomy, implant reconstruction surgeries of mammary gland and may necessitate modifying the approach during mammoplasty. The early detection of this variant muscle is necessary for assessing proper dissection planes in breast surgeries and radiological examination. Hereby, we report a case of unilateral rectus sternalis muscle. The muscle originated from the fascia covering external oblique muscle inserted in to the sternum at the manubrio sternal joint; the muscle belly was 10 cm in length and 1.5 cm in width.